2020
DOI: 10.1177/1077558720907183
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and Needs of Families in Nursing Homes: An Integrative Review

Abstract: A better understanding of the expectations and needs of the families of nursing home residents is needed for a constructive and sustainable relationship of mutual trust. The objective of this study was to understand the expectations of families of nursing home residents described in the literature. A systematic integrative review of the literature was conducted. After a rigorous selection made by two researchers, independently, 53 articles were selected out of 1,094 results. The expectations of families are qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…As mentioned in other studies regarding caring for a loved one in the nursing home (Havreng-Théry et al, 2021;Reid & Chappell, 2017;Rosén et al, 2019), it was important for all the daughters that the mother received the care she needed, preserving dignity to allow her to feel alive and respected.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As mentioned in other studies regarding caring for a loved one in the nursing home (Havreng-Théry et al, 2021;Reid & Chappell, 2017;Rosén et al, 2019), it was important for all the daughters that the mother received the care she needed, preserving dignity to allow her to feel alive and respected.…”
Section: Discussionmentioning
confidence: 94%
“…Family members want to be partners in the care process (Graneheim et al, 2014;Kiljunen et al, 2018) and establish a relationship with health professionals built on reliability. Most important is that the loved one receives the care needed to preserve dignity, allowing the 1 Faculty of Graduate Studies in Health Sciences, University of Akureyri, Iceland 2 Faculty of Nursing, University of Akureyri, Iceland individual to feel alive and respected (Havreng-Théry et al, 2021;Reid & Chappell, 2017). The certainty that the loved one is well cared for and one's own participation can intensify relationships (Havreng-Théry et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] Physical factors in the artificial and natural environment contribute to creating a sense of home in such institutions. [40][41][42] Especially, the use of communal areas in natural and artificial environments can positively affect the feeling of being at home. 43,44 To create a sense of home in elderly care or nursing homes is important, however, several research indicated that the elderly individuals still struggled to achieve such feeling.…”
Section: Problems About Ageingmentioning
confidence: 99%
“…Nursing homes (NH) are settings for long-term medical treatment and nursing care for the frail older persons in our society, and at the same time a home where the residents spend the last phase of their lives. Hence, NH are expected to provide quality care, complying with the human dignity of the resident, and collaboration, honesty, and mutual confidence that ties together families and staff [1]. Still, a growing amount of research has revealed that abuse and neglect frequently occur in NH in many countries [2][3][4][5][6][7][8][9][10], including Norway [11][12][13].…”
Section: Introductionmentioning
confidence: 99%